The Effect of Service Quality And Servicescape on Impulsive Buying Behavior with Shopping Emotion as Intervening Variable for Consumers Store of Fashion Uniqlo Duta Mall Banjarmasin, South Kalimantan - Diany, Adista Anjar; Sucidha, Irma; Kosasih, Nico (Cattleya Darmaya Fortuna, 2025)
The rapid growth of the retail business requires effective strategies to capture market share. This study aims to analyse the effect of service quality and servicescape on impulse buying behaviour through shopping emotions in Uniqlo Duta Mall Banjarmasin consumers. The research method uses primary and secondary data from questionnaires and literature studies with 111 respondents. The results of the analysis show that service quality and servicescape have a positive and significant impact on impulse buying behaviour with shopping emotions as an intermediary variable.